PELATIHAN ENGLISH BUSINESS LETTER KEPADA TENAGA KEPENDIDIKAN UNU PURWOKERTO - Dinar Faiza; Ade Christanty Yudha Bestari; Meilina Haris Mayekti (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Community Partnership Program (PKM) entitled “English Business Letter Training for Education Staff in UNU Purwokerto” aims to provide English language education, especially regarding English Business Letters for education staff. There was still a lack of English language skills and that it still needed additional knowledge regarding the rules of writing Business Letter in English. It is the main reason for taking topic. This PKM activity supported the vision of UNU Purwokerto about producing superior human resources with a global perspective. Moreover, UNU Purwokerto has accepted students from abroad who definitely need administration and communication in English. The object of PKM is UNU Purwokerto's educational staff, totaling 15 people who are representatives from each section. Providing a training using the fun learning method is aimed to maximize the learning process. Through this PKM activity, it is hoped that human resource competency will be increased and performance will be maximized to support the better quality of the university.